Vanishing bone : conquering a stealth disease caused by total hip replacements - Harris, William H. (William Hamilton), 1927- (New York, NY : Oxford University Press, 2018)
" When dozens of holes appeared in a patient's femur alongside his hip prosthesis, experts were baffled as such a phenomenon had never been seen before. Over the first four decades of total hip surgery, the severe bone destruction multiplied, crippling many thousands of patients. Eventually identified as "periprosthetic osteolysis," this devastating disease affected over 1 million patients and was the leading cause of failure in total hip surgery. While total hip surgery dramatically reversed severe arthritis of the hip, the same operation simultaneously created a relentless 'particle generator' in the body. Ironically, in the effort to do good, doctors were simultaneously doing major harm. Vanishing Bone : Conquering a Stealth Disease Caused by Total Hip Replacements takes readers on a detective adventure in contemporary medical science, from the identification of the cause of the disease through the complex process of affecting its cure. Dr. William H. Harris and his colleagues played an important role in solving the mystery of this disease, pointing to its molecular biology, recognizing the unusual wear of the prostheses, and ultimately developing a new material for use in the manufacture of hip implants. With more than 6 million people walking on this stable, low-wear material, the disease has been virtually eliminated among those with total hip replacements worldwide. Diseases are rarely observed, revealed, and eliminated in one lifetime. Vanishing Bone tells the captivating story of one such disease through an engaging account of scientific and medical innovation."--
Keywords: Total hip replacement; Bone resoption; Print books